Ask Questions, Get Answers

Home  >>  CBSE XII  >>  Math  >>  Integrals

Integrate the function $(3x-2)\sqrt{x^2+x+1}$

1 Answer

  • Method of substitution:
  • Given $\int f(x)dx$ can be transformed into another form by changing independent variable x to t by substituting x=g(t).
  • Consider $I=\int f(x)dx.$
  • Put x=g(t) so that $\frac{dx}{dx}=g'(t).
  • dx=g'(t)dt.
  • Thus $ I=\int f(g(t).g'(t))dt.$
Given $ I=\int (3x-2)\sqrt {x^2+x+1}dx.$
Let $x^2+x+1=t $.
Hence$ (2x+1)dx=dt.$
Now we can Substitute for $ t $and $dt$ in $ I$ we get,
$I=\int \large\frac{3}{2}$$(2x-\large\frac{4}{3}$$)\sqrt{x^2+x+1}dx.$
$I= \large\frac{3}{2}$$\int(2x+1-\large\frac{7}{3}$$)\sqrt{x^2+x+1}dx.$
$I= \large\frac{3}{2}$$\big[\int(2x+1)\sqrt{x^2+x+1}dx.-\int\large\frac{7}{3}$$\sqrt{x^2+x+1}dx\big]$
$\;\;\;=\large\frac{3}{2}$$\big[\int (t)^\frac{1}{2},dt-\large\frac{7}{3}\int\sqrt{x^2+x+1}dx\big]$
On integrating we get,
Substituting back for t we get,
answered Mar 21, 2014 by rvidyagovindarajan_1
edited Mar 21, 2014 by rvidyagovindarajan_1

Related questions